Una lezione al professore o una lezione dal professore? - Franco Longoni (Annali Online dell'Università di Ferrara. Sezione Lettere)
The exhibition Cranach: a Different Renaissance drew the attention on a masterpiece where the famous story of Aristotle and Phyllis is pictured, a legend born in the great stream of Alexander’s life history, a narrative stream running in the underground of European culture from the classical period to emerge here and there in different places and different times under different forms, to be interpreted time by time through different keys under the philosophical, anthropological, literary, artistic, psychological profile: from the medieval poem of Henri d’Andeli The Lay of Aristote, to the mythic film The Blue Angel based on the also famous book of Heinrich Mann Professor Unrat, the fatidic professor waiting at the door of the only woman who could give him a lesson, passing through a lot of similar cases as the one illustrated by the notorious photograph picturing Nietzsche Beyond Good and Evil subjugated together with Paul Rée by Lou Andreas-Salomé.